Preparing Students to Write in Professional Environments (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2018)
American businesses annually spend billions of dollars in efforts to improve their employees’ writing abilities in the workplace. Current methods of writing instruction are not adequately preparing students for professional environments, and in order to alleviate these issues, adaptations must be made in secondary classrooms to foster writing self-efficacy and mastery. Through the use of reflective writing activities, meaningful assignments, and lesson plans incorporating technology, teachers can help students develop as writers and better prepare them for the workforce.